(untitled) (BIRDEM Medical Journal, 2019)
Background: Caulerpa recemosa, also known as sea grape, is a stout straggling prostrate shrubby plant with spinous stipules and uniaxial siphonous thallus, mostly divided into a creeping axis (stolon), with rhizoids and erect shoots (fronds), either nude, leaf-like or with grape or feather-like ramuli. Caulerpa racemosa has erect fronds up to 9-13 cm high bearing un-crowded vesiculate ramuli that are radially arranged. Fronds are slightly inflated above the attachment to the stolon which are fixed to the substrate by thin short rhizoids. It is collected from St. Martin’s Island locally called ‘Narikel Jinjira’, located on the southernmost tip of Bangladesh for the present study, ethanol extract of Caulerpa recemosa has been screened for its hypolipidemic activity. Methods: Hypolipidemic activity was screened by inducing hyperlipidemia with the help of atherogenic diet in wistar albino rats and serum levels of various biochemical parameters such as total cholesterol, triglycerides, low density lipoprotein and high density lipoprotein cholesterol were determined. Atherogenic index shows the measure of the atherogenic potential of the drugs. Results: Ethanol extract showed significant (p < 0.01) hypolipidemic effect by lowering the serum levels of biochemical parameters such as significant reduction in the level of serum cholesterol, triglyceride, low density lipoprotein and increase in high density lipoprotein level which was similar to the standard drug atorvastatin. Ethanol extract exhibited significant atherogenic index andpercentage protection against hyperlipidemia. Preliminary phytochemical analysis revealed the presence of phytoconstituents such as steroids, flavonoids, glycosides, alkaloids, phenoliccompounds. Conclusion: The overall experimental results suggest that the biologically active phytoconstituents such as flavonoids, glycosides alkaloids present in the ethanolic extract of Caulerpa racemosa may be responsible for the significant hypolipidemic activity and the results may justify the use of Caulerpa racemosa as a significant hypolipidemic agent. Birdem Med J 2019; 9(3): 197-201